The Quality of Accounting Education in Iraqi Universities - Jassim Mohammed, Laith; Ahmed Mohammed Al-Ani, Safaa (Journal of Economics and Administrative Sciences, 2022)
The aim of the research is to assess the quality of the university accounting education system in Iraq. The researcher relied on the opinions of a sample of academics specialized in this field by preparing a checklist focusing on a set of axes that would affect the quality of accounting education in the Iraqi environment. The most prominent finding of the research is that the quality of accounting education in Iraqi universities is medium and differs from one university to another in some quality components. In addition, the prescribed curricula and study plans applied in the accounting departments do not live up to the required level, as the largest proportion of those curricula are theoretically devoid of practical exercises that contribute to the quality of accounting education.